Urinary chloride concentration and progression of chronic kidney disease: results from the KoreaN cohort study for Outcomes in patients With Chronic Kidney Disease. Issue 4 (17th December 2019) - Joo, Young Su; Kim, Jinseok; Park, Cheol Ho; Yun, Hae-Ryong; Park, Jung Tak; Chang, Tae Ik; Yoo, Tae-Hyun; Sung, Su-Ah; Lee, Joongyub; Oh, Kook-Hwan; Kim, Soo Wan; Kang, Shin-Wook; et al.
Abstract: Background: Urinary chloride is regulated by kidney transport channels, and high urinary chloride concentration in the distal tubules can trigger tubuloglomerular feedback. However, little attention has been paid to urinary chloride as a biomarker of clinical outcomes. Here, we studied the relationship between urinary chloride concentration and chronic kidney disease (CKD) progression. Methods: We included 2086 participants with CKD from the KoreaN cohort study for Outcomes in patients With Chronic Kidney Disease. Patients were categorized into three groups, according to baseline urinary chloride concentration tertiles. The study endpoint was a composite of ≥50% decrease in estimated glomerular filtration rate from baseline values, or end-stage kidney disease. Results: During a median follow-up period of 3.4 years (7452 person-years), 565 participants reached the primary endpoint. There was a higher rate of CKD progression events in the lowest and middle tertiles than in the highest tertile. Compared with the lowest tertile, the highest tertile was associated with 33% [95% confidence interval (CI) 0.49–0.90] lower risk for the primary outcome in a cause-specific hazard model after adjustment for confounding variables. In addition, for every 25 mEq/L increase in urinary chloride concentration, there was 11% (95% CI 0.83–0.96) lower risk for CKD progression. This association was consistent in a time-varying model. Urinary chloride concentration correlated well with tubule function and kidney injury markers, and its predictive performance for CKD progression was comparable to that of these markers. Conclusions: In this hypothesis-generating study, low urinary chloride concentration was associated with a higher risk for CKD progression.